21st century techniques for dental implants: Alternative to sinus lift for rehabilitation with short dental implants (Research, Society and Development, 2024)
Introduction: The absence of teeth can harm a person's self-esteem, which can result in low confidence, emotional distress and social anxiety. There is no doubt that dental implants are currently the most suitable solution to mitigate the problem of tooth loss. Objective: to present, through a literature review, what is the relationship between the clinical study of breast lifting and the installation of short implants as an alternative to this surgical technique, taking into account surgery time, post-operative period, success of the implants and prosthetic quality. Methodology: The selection criteria for the articles that made up this work followed the inclusion and exclusion criteria. Following the inclusion criteria, articles available in Portuguese, English and Spanish were selected, which discussed breast lifting techniques for the installation of long implants in relation to the installation of short implants without the need for bone grafts. Articles that were published between 2010 and 2020 were also considered. Final considerations: It was possible to observe that the present article presents strong points and eminences that suggest the use of short implants, even in areas of poor bone quality and for patients who, for some reason, This is why they cannot undergo complex oral surgical procedures. .